Barriers Limiting Audit of Non-Financial Reports on Polish Auditing Services Market - Anna BARTOSZEWICZ; Anna RUTKOWSKA-ZIARKO (Communications of International Proceedings, 2021)
The aim of the article is to identify of the barriers conducting of non-financial reports audits in Poland as well as identification of the percentage of audit firms being under audit supervision, which are  performing this kind of services in Poland. The article identifies the entities operating in the Polish audit market in terms of selected features. The authors provided answers to three main research questions: What percentage of audit firms in Poland carry out the verification of non-financial reports? How many years of audit experience do the firms providing audit services have? What are the barriers of conducting non-financial reports audit? To achieve the objective, an empirical study was conducted among audit firms which are under the supervision of the Polish Agency of Audit Oversight. The theoretical basis of the article included a literature study on the audit of non-financial reports as well as an analysis of regulations governing this subject matter in Poland. The obtained study results indicate that only 2.3% of audit firms perform audits of CSR reports. The barriers limiting the performance of this type of services are among other  the low demand in this regard as well as by insufficient staff in audit firms.
Keywords: audit; non-financial reporting; CSR; Corporate Social Responsibility.